Can someone show me the step to solving this equation because I am just not getting it. My teacher is confusing me, so I need someone else to explain it in a different uncomplicated way. y-1/x+3 = -3/4.Thanks so much you guys for the help.

1 answer

You must use parentheses when typing equations like this; otherwise we can't be sure what the problem is.

Is the equation
(y-1)/(x+3) = -3/4, or
y - (1/x) + 3 = -3/4 ?
Those are two entirely different equations.

If it is the former, get rid of the denominator to write
y - 1 = -3x/4 -9/4

Then combine the constants on one side.
y = -3x/4 -5/4

You cannot solve a single equation for two unknowns. Do they want an equation for y in terms of x, or vice versa?
Similar Questions
  1. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 3 answers
  2. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 3 answers
more similar questions